2014
DOI: 10.1186/2193-1801-3-302
|View full text |Cite
|
Sign up to set email alerts
|

Antityphoid and radical scavenging properties of the methanol extracts and compounds from the aerial part of Paullinia pinnata

Abstract: Paullinia pinnata Linn (Sapindaceae) is a medicinal plant, locally used in the West Region of Cameroon for the treatment of typhoid fever. This work was designed to evaluate the antityphoid and antioxidant activities of the extracts and compounds of P. pinnata.The methanol extracts of the leaves and stems were tested for antityphoid and antioxidant activities. Compounds were isolated, and their structures elucidated by analysis of spectroscopic data in conjuction with literature data and tested for the same ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…The compounds isolated in the present study were formerly isolated from other plants and the biological activities of some were demonstrated [23, 24]. Besides, in our previous investigation, their antityphoid and antioxidant properties were demonstrated [9]. P. pinnata extract have been proven to possess antioxidant [25] and vascular relaxation [2] properties.
Figure 1 Chemical structures of compounds from the leaves (1–3) and stems (4–7) of P. pinnata.
…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The compounds isolated in the present study were formerly isolated from other plants and the biological activities of some were demonstrated [23, 24]. Besides, in our previous investigation, their antityphoid and antioxidant properties were demonstrated [9]. P. pinnata extract have been proven to possess antioxidant [25] and vascular relaxation [2] properties.
Figure 1 Chemical structures of compounds from the leaves (1–3) and stems (4–7) of P. pinnata.
…”
Section: Resultsmentioning
confidence: 78%
“…As a result of our interest in the chemical and biological investigation of this plant, a methylinositol ( 1 ), steroidal terpenoids ( 2 and 4 ), and oleanane triterpenoids ( 3 , 5 – 7 ) were isolated from its leaf and stem methanol extracts. In our previous studies, the antityphoid and antioxidant properties of these compounds were evaluated [9]. The extracts, fractions and all the compounds were evaluated for their antimicrobial activities against eight bacteria, five yeasts and five dermatophytes species and the results are reported herein.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the bacterial burden of faeces in infected and untreated rats may be explained by the protective action of their immune system against the pathogens (Lunga et al, 2014). The in vitro and in vivo analyses of antibacterial activity revealed the antibacterial and therapeutic potential of A. leiocarpa.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these groups of compounds in the methanol extract of P. pinnata could explain the dose-dependent periodic eradication of typhoid fever and thus the weight gain observed in this study. Besides, many compounds from this extract were isolated; including oleanane-type triterpenoid saponins and a steroidal saponin with remarkable antisalmonella activities in vitro 4 . This phenomenon was further enhanced by the eradication of the disease condition since it was found that typhoid fever induces weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant properties of the methanol extract of the leaves and antibacterial activity of fatty acids from the roots of P. pinnata have been investigated 2,3 . In the ongoing studies, potential antityphoid properties of the methanol extract from the leaves of P. pinnata, both in vitro on four species of Salmonella (S. typhi, S. paratyphi A, S. paratyphi B and S. typhimurium) and in vivo on a S. typhimurium-induced typhoid model in Wistar rats was demonstrated 4 . In vitro, the Minimum Inhibitory Concentrations (MICs) ranged from 48-3125 μg mLG 1 , while in vivo, the extract could eradicate the disease condition after 4 and 5 days, respectively at a daily oral dose of 446 and 223 mg kgG 1 b.wt.…”
Section: Introductionmentioning
confidence: 99%